Pemutusan Hubungan Kerja Yang Dilakukan Pelaku Usaha Kepada Tenaga Kerja Melalui Media Online Sesuai Dengan Ketentuan Undang-Undang - Johnny Pieter Sual; Merry Tjoanda; Agustina Balik (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Unilateral termination of employment relations is absolutely not allowed and is very clear, except for certain circumstances that compel the dismissal to be carried out, as stipulated in the